Thymidylate synthase predictive power is overcome by irinotecan combination therapy with S-1 for gastric cancer - Ichikawa, W (Nature Publishing Group, 2004)
The predictive values of thymidylate synthase (TS) and dihydropyrimidine dehydrogenase (DPD) gene expressions were retrospectively evaluated in patients with gastric cancer treated by a regimen containing S-1. The study population consisted of 53 patients registered into different two phase II studies for metastatic gastric cancer; 27 patients treated by S-1-alone study: 26 patients treated with S-1 combined with irinotecan (CPT-11). TS and DPD gene expressions in primary tumours were measured by the real-time reverse transcription PCR method. There was no statistical difference in DPD gene expression in terms of response in cases treated with S-1 alone and those treated with S-1 plus CPT-11. TS mRNA of responding tumours was lower than that of nonresponding ones when treated with S-1 (P<0.005). In the S-1-alone group, taking TS cutoff as the median values, the response rate in the low TS group was 50%, but only 8% in the high TS group (P<0.05). Patients with low TS gene expression survived longer than those with high TS gene expression (P<0.0001). However, there was no statistically significant difference in response rate and survival between patients with low TS tumours and those with high TS tumours, when the cutoff was taken as the median value of TS gene expression in the group treated with S-1 plus CPT-11. In conclusion, treatment effects of S-1 monotherapy for gastric cancer were determined by the status of TS gene expression, regardless of DPD gene expression. TS predictive power was overcome by CPT-11 combination therapy with S-1.